EPO662: Electrical Engineering Laboratory V / College of Engineering - UiTM, College of Engineering (2023)
This course provides the necessary hands-on experience relating to Power Electronics, Power Drives, High Voltage and Power Utilization concepts taught in theoretical lectures.